Neurocognitive and functional impairment in adult and paediatric tuberculous meningitis [version 1; peer review: 2 approved] - Angharad G. Davis; Sam Nightingale; Priscilla E. Springer; Regan Solomons; Ana Arenivas; Robert J. Wilkinson; Suzanne T. Anderson; Felicia C. Chow; Tuberculous Meningitis International Research Consortium (Wellcome Open Research, 2019)
In those who survive tuberculous meningitis (TBM), the long-term outcome is uncertain; individuals may suffer neurocognitive, functional and psychiatric impairment, which may significantly affect their ability to lead their lives as they did prior to their diagnosis of TBM. In children who survive, severe illness has occurred at a crucial timepoint in their development, which can lead to behavioural and cognitive delay. The extent and nature of this impairment is poorly understood, particularly in adults. This is in part due to a lack of observational studies in this area but also inconsistent inclusion of outcome measures which can quantify these deficits in clinical studies. This leads to a paucity of appropriate rehabilitative therapies available for these individuals and their caregivers, as well as burden at a socioeconomic level. In this review, we discuss what is known about neurocognitive impairment in TBM, draw on lessons learnt from other neurological infections and discuss currently available and emerging tools to evaluate function and cognition and their value in TBM. We make recommendations on which measures should be used at what timepoints to assess for impairment, with a view to optimising and standardising assessment of neurocognitive and functional impairment in TBM research.